Technology Readiness Index of Agricultural Extension Officers in Bandung City, Indonesia, towards Digitalization of the “Buruan Sae” Program - Parman Sukarno; Rahmat Yasirandi; Rio Guntur Utomo; Muhammad Al Makky; Ridha Muldina Negara; Sri Rezeki (agriTECH, 2022)
Currently, “Buruan Sae” is a leading program in Bandung City, during the pandemic, this program was used to solve the problem of food security for every community. The government also promotes every community to implement urban farming in the city. Meanwhile, digitization is a step that is expected to be carried out in the future. To prepare for the transformation in this direction, the initial step is to measure readiness. Therefore, this study aims to determine the readiness of Agricultural Extension Officers (AOE) in Bandung as a necessary initial step in assisting the digital transformation of the “Buran Sae” program. AOE from the Department of Food and Agriculture were used as the sample population considering that they are the “spearhead” of this program. Using the Technology Readiness Index (TRI) Model, the value obtained was 3.365, which can be categorized as Medium Technology Readiness group. The amount of Explorers group namely 37.5% indicated that the majority of extension officers will accept the technology quickly. Furthermore, no part of the population can completely resist technological change as implied by the absence of the Laggards group. In the future, the results are expected to become a fundamental basis for the Department of Food and Agriculture to achieve digital transformation and this program will continue to be the main answer to every community’s problem of food and agriculture.